Impact of antibiotic prophylaxis on gut microbiota in colorectal surgery: insights from an Eastern European stewardship study - Văcărean-Trandafir, Irina Cezara; Amărandi, Roxana-Maria; Ivanov, Iuliu Cristian; Dragoș, Loredana Mihaiela; Mențel, Mihaela; Iacob, Ştefan; Muşină, Ana-Maria; Bărgăoanu, Elena-Roxana; Roată, Cristian Ene; Morărașu, Ștefan; Țuțuianu, Valeri; Ciobanu, Marcel; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionAntibiotic overuse is driving a global rise in antibiotic resistance, highlighting the need for robust antimicrobial stewardship (AMS) initiatives to improve prescription practices. While antimicrobials are essential for treating sepsis and preventing surgical site infections (SSIs), they can inadvertently disrupt the gut microbiota, leading to postoperative complications. Treatment methods vary widely across nations due to differences in drug choice, dosage, and therapy duration, affecting antibiotic resistance rates, which can reach up to 51% in some countries. In Romania and the Republic of Moldova, healthcare practices for surgical antibiotic prophylaxis differ significantly despite similarities in genetics, culture, and diet. Romania's stricter healthcare regulations result in more standardized antibiotic protocols, whereas Moldova's limited healthcare funding leads to less consistent practices and greater variability in treatment outcomes.MethodsThis study presents the results of a prospective cross-border investigation involving 86 colorectal cancer patients from major oncological hospitals in Romania and Moldova. We analyzed fecal samples collected from patients before and 7 days post-antibiotic treatment, focusing on the V3–V4 region of the 16S rRNA gene.ResultsOur findings indicate that inconsistent antibiotic prophylaxis policies—varying in type, dosage, or therapy duration—significantly impacted the gut microbiota and led to more frequent dysbiosis compared to stricter prophylactic antibiotic practices (single dose, single product, limited time).DiscussionWe emphasize the need for standardized antibiotic prophylaxis protocols to minimize dysbiosis and its associated risks, promoting more effective antimicrobial use, particularly in low- and middle-income countries (LMICs).